When iodide meets bromide: Halide mixing facilitates the light-induced decomposition of perovskite absorber films. (August 2021) - Akbulatov, Azat F.; Ustinova, Marina I.; Gutsev, Lavrenty; Tsarev, Sergey A.; Dremova, Nadezhda N.; Zhidkov, Ivan; Luchkin, Sergey Yu.; Ramachandran, Bala R.; Frolova, Lyubov; Kurmaev, Ernst Z.; Stevenson, Keith J.; Aldoshin, Sergey M.; et al.
Abstract: APbX3 lead perovskites, where A is either an organic (methylammonium MA + and formamidinium FA + ) or an inorganic (Cs + ) species, have recently emerged as highly promising photovoltaic materials. This interest is related to the exceptionally high power conversion efficiency (> 25%) demonstrated recently in the case of mixed-cation and mixed-halide perovskites. However, the poor intrinsic stability of complex lead halides remains a major hindrance in the commercialization of this emerging photovoltaic technology. An intense research effort is currently focused on revealing the origins and mechanistic aspects of the various pathways of degradation occurring in perovskite solar cells. In this paper, we present a systematic comparative study of a series of mixed-cation perovskite systems: MA0.15 FA0.85 PbI2.55 Br0.45, Cs0.1 MA0.15 FA0.75 PbI2.55 Br0.45, Cs0.15 FA0.85 PbI2.55 Br0.45, MA0.15 FA0.85 PbI3, Cs0.1 MA0.15 FA0.75 PbI3, and Cs0.15 FA0.85 PbI3 all of which deliver high photovoltaic efficiencies in devices. Using a set of complementary analytical techniques, we demonstrate that bromide-containing mixed-halide perovskites have much lower photostability when compared to the equivalent iodide-based materials. The light-induced photochemical aging produced metallic lead as one of the final decomposition products in the case of all the studied complex lead halides except for Cs0.15 FA0.85 PbI3, which demonstrated outstanding stability under white light exposure. Theoretical calculations of the bromide-containing mixed-halide perovskites indicated that hole-coupling drives the formation of interstitial-vacancy halide pair defects to become more thermodynamically favorable, thus leading to the accelerated degradation of the halide-mixed perovskites. The obtained results demonstrate the usefulness of compositional engineering as a promising approach to boost the operational stability of perovskite solar cells and pave the way towards their successful commercialization. Graphical Abstract: ga1 Highlights: Intrinsic stability is studied for a series of mixed cation complex lead halides. Incorporation of Br − anions in perovskite lattice reduces material photostability. Stability is increasing in the order MAx FA1−x PbX3 < Csx MAy FA1−x−y PbX3 < Csx FA1−x PbX3 . DFT calculations showed that hole-coupling degrades the mixed-halide FAPb(I/Br)3 perovskite. Hole-coupling degrades mixed-halide perovskites as shown by DFT calculations.